Detection of mRNAs encoding peroxisomal proteins by non-radioactive in situ hybridization with digoxigenin-labelled cRNAs - Baumgart-Vogt, Eveline; Schad, Arno; Völkl, Alfred; Fahimi, H. Dariush (Histochemistry and cell biology, 1997)
We have used a non-radioactive in situ hybridization (ISH) protocol for the detection of mRNAs encoding proteins localized in peroxisomes. In this presentation the literature on detection of ”peroxisomal mRNAs” is reviewed and the results obtained by application of the non-radioactive method are compared with those obtained by hybridization with radioactive probes. Moreover, the special processing conditions and the application of the method for the specific visualization of mRNAs coding for several peroxisomal proteins with different abundance levels and distinct tissue distributions are presented. The combination of the following technical details in the ISH procedure were found to be essential for obtaining optimal sensitivity and good histological quality of the preparations: (a) perfusion-fixation with a fixative containing 4% depolymerized paraformaldehyde/0.05% glutaraldehyde, (b) the use of paraffin embedding instead of frozen sections, (c) specific proteinase K-digestion time for each tissue, and (d) the use of digoxigenin-labelled cRNA probes (hydrolyzed to a length of about 200 bases) for detection. By using this technique, we were able to localize several peroxisome-specific mRNAs with different degrees of abundance: (1) high-level (catalase and urate oxidase) and (2) low-level (all β-oxidation enzymes and the 70-kDa peroxisomal membrane protein) in rat liver and kidney. The specificity of the method was confirmed by the negative results obtained with corresponding sense controls and the distinct positive staining patterns obtained for albumin and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) mRNAs. All transcripts for mRNAs encoding peroxisomal proteins were localized to the cytoplasm of hepatocytes, with all nuclei as well as epithelial cells of bile ducts and sinusoidal cells remaining negative. In rat kidney, the catalase transcripts were confined to proximal tubular epithelial cells, which is consistent with the high abundance of peroxisomes in this part of the nephron. In contrast, no transcripts for urate oxidase were present in the kidney, corresponding to the absence of that protein in this organ. The transcripts for GAPDH on the other hand were localized in proximal and distal tubular epithelial cells as well as in collecting ducts. The application of this technique to the rat adrenal gland and testis in recent unpublished studies have revealed exclusive localization of catalase transcripts to the adrenal cortex and to interstitial cells of Leydig, which are known to be rich in microperoxisomes. These observations demonstrate the suitability of this technique for accurate localization of mRNAs encoding peroxisomal proteins and for the analysis of alterations in the expression of the corresponding genes under different experimental conditions.
Gesehen am 09.01.2025